Development on the reconstruction of photothermal imaging method for subsurface structure - Kim, Moojoong; Yoo, Jaisuk; Kim, Dong Kwon; Kim, Hyunjung (Journal of Visualization, 2019)
Abstract: The photothermal imaging technique is a nondestructive inspection technique that visualizes the inside of a metal by utilizing the photothermal effect. Although the concept of photothermal imaging techniques has been proposed, systematic research on the characteristics thereof has not been conducted. This study attempts to enhance the measurement and reconstruction process for a photothermal imaging method. To detect the edge of a subsurface pattern more accurate, low-pass FFT (fast Fourier transform) filter for noise reduction of measured data, and derivative detectors are adopted for the reconstruction of photothermal imaging. The adopted methods are applied to and visualize 20 mm × 25 mm × 1.5 mm copper block including radius 5 mm, height 1 mm cylindrical resin as a subsurface pattern. The results show that the developed method can detect the edge of the resin subsurface 50% more accurately than the previous reconstruction method for photothermal imaging. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Derivative edge detector; Filter; Imaging techniques; Noise; Photothermal; Reconstruction